2008
DOI: 10.1111/j.1365-2699.2008.01885.x
|View full text |Cite
|
Sign up to set email alerts
|

Inferring dispersal: a Bayesian approach to phylogeny‐based island biogeography, with special reference to the Canary Islands

Abstract: Aim Oceanic islands represent a special challenge to historical biogeographers because dispersal is typically the dominant process while most existing methods are based on vicariance. Here, we describe a new Bayesian approach to island biogeography that estimates island carrying capacities and dispersal rates based on simple Markov models of biogeographical processes. This is done in the context of simultaneous analysis of phylogenetic and distributional data across groups, accommodating phylogenetic uncertain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
219
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 213 publications
(238 citation statements)
references
References 120 publications
(193 reference statements)
7
219
1
1
Order By: Relevance
“…Funk and Wagner (1995) found that patterns of island colonization in these islands were highly congruent across multiple lineages, proceeding from one island to the next along the island chain. Similarly, Sanmartín et al (2008) inferred highly concordant, non-random colonization patterns across numerous organisms endemic to the Atlantic Canary Islands.…”
Section: Vicariance and Cladistic Biogeographymentioning
confidence: 99%
See 3 more Smart Citations
“…Funk and Wagner (1995) found that patterns of island colonization in these islands were highly congruent across multiple lineages, proceeding from one island to the next along the island chain. Similarly, Sanmartín et al (2008) inferred highly concordant, non-random colonization patterns across numerous organisms endemic to the Atlantic Canary Islands.…”
Section: Vicariance and Cladistic Biogeographymentioning
confidence: 99%
“…Biogeographical models, however, are best seen not as constraints over the data but as alternative hypotheses to explain the data (Sanmartín et al 2008). A more important limitation is how to balance the complexity of biogeographic models with the inferential power of the method (Ree and Sanmartín 2009).…”
Section: Parsimony In Biogeographymentioning
confidence: 99%
See 2 more Smart Citations
“…Alternatively, Sanmartín et al [13], in a similar data analysis, model all strata jointly by imposing the same migration graph and rates to all strata of the analysis. This method effectively combines information from all strata to improve rate estimates.…”
Section: Introductionmentioning
confidence: 99%